THE ROLE OF CONTEXT IN WORD MEANING CONSTRUCTION: A CASE STUDY - Porto Requejo, Maria Dolores (International Journal of English Studies, 2009)
The role of context in the interpretation of a linguistic unit has long been considered, even if from different perspectives: from the view that regards context as an extralinguistic feature, to the position that meaning is only meaning in use and therefore, pragmatics and semantics are inseparable. Still, context, both linguistic and situational, is often considered as an a posteriori factor in linguistic analysis. However, when language is studied in use, context always comes first, directing the process of meaning construction from the very beginning. In the present paper, a case study will provide evidence for these claims.